2012
DOI: 10.1016/j.ijhydene.2011.12.106
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the NaBO2–H2O phase diagram for optimized yield in the H2 generation through NaBH4 hydrolysis

Abstract: The binary phase diagram NaBO 2-H 2 O at ambient pressure, which defines the different phase equilibria that could be formed between borates, end-products of NaBH 4 hydrolysis, has been reviewed. Five different solid borates phases have been identified: NaBO 2 •4H 2 O (Na[B(OH) 4 ]•2H 2 O), NaBO 2 •2H 2 O (Na[B(OH) 4 ]), NaBO 2 •2/3H 2 O (Na 3 [B 3 O 4 (OH) 4 ]), NaBO 2 •1/3H 2 O (Na 3 [B 3 O 5 (OH) 2 ]) and NaBO 2 (Na 3 [B 3 O 6 ]), and their thermal stabilities have been studied. The boundaries of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The pressure in the proposed system is one order of magnitude smaller than in conventional hydrogen storage pressure vessels. This is also supported by Andrieux et al (2012), who revised the phase diagram of NaBO 2 -H 2 O in 2012 and found that at 250 ± 2°C, the hydrated metaborate consists only of pure NaBO 2 and vapour [59]. The temperature dependence of the vapour pressure of NaBH 4 or NaBO 2 solution is not known to the author, but from the results of Marrero-Alfonso et al (2007) and Andrieux (2012) [47,58], where hydrate formation and dehydration of NaBO 2 were investigated, it can be inferred that, at given temperature, it is much higher than of pure water.…”
Section: Restrictions and Assumptionssupporting
confidence: 63%
See 1 more Smart Citation
“…The pressure in the proposed system is one order of magnitude smaller than in conventional hydrogen storage pressure vessels. This is also supported by Andrieux et al (2012), who revised the phase diagram of NaBO 2 -H 2 O in 2012 and found that at 250 ± 2°C, the hydrated metaborate consists only of pure NaBO 2 and vapour [59]. The temperature dependence of the vapour pressure of NaBH 4 or NaBO 2 solution is not known to the author, but from the results of Marrero-Alfonso et al (2007) and Andrieux (2012) [47,58], where hydrate formation and dehydration of NaBO 2 were investigated, it can be inferred that, at given temperature, it is much higher than of pure water.…”
Section: Restrictions and Assumptionssupporting
confidence: 63%
“…There, the so-called water excess factor x was introduced, which is commonly set to 2, when the hydrolysis is carried out near RT. [59]. Considering these facts, the hydrolysis reaction equation used in the following study is assumed as…”
Section: Restrictions and Assumptionsmentioning
confidence: 99%
“…This is due to the hydration of the borate by-products, which are in the forms NaBO 2 Á2H 2 O and NaBO 2 Á4H 2 O [35,36]. The first issue is the low net GHSC of the system NaBH 4 -H 2 O.…”
Section: Sodium Borohydridementioning
confidence: 99%
“…The first issue is the low net GHSC of the system NaBH 4 -H 2 O. This is due to the hydration of the borate by-products, which are in the forms NaBO 2 Á2H 2 O and NaBO 2 Á4H 2 O [35,36]. For example, the GHSC of NaBH 4 -H 2 O is 7.3 wt% when 4 mol H 2 O per mol NaBH 4 are required for the hydrolysis reaction (Eq.…”
Section: Sodium Borohydridementioning
confidence: 99%
“…To increase the energy density of this H 2 generator system, the NaBH 4 concentration has to be maximized. For this, one of the main challenges remains to increase the NaBH 4 concentration of alkaline aqueous solution without drawbacks due to the by-products crystallization, NaBO 2 .yH 2 O, with the pseudo hydration degree y = 0, 1/3, 2/3, 2 and 4 [5]. Sodium hydroxide is added to the solution to limit the self-decomposition of NaBH 4 , thus stabilizing the system.…”
mentioning
confidence: 99%